Structural Diversity of Flowers and Pollination Ecology in Podostemaceae - Khanduri , P.; Uniyal, P. L.; Roy, S. K.; Tandon, R. (Rheedea, 2025)
Podostemaceae, or “river-weeds,” are a diverse family of freshwater angiosperms adapted to fast-flowing tropical and subtropical rivers. With over 300 species, they exhibit remarkable morphological variation across regions, especially between New World and Old-World taxa. Their life-cycle is tightly synchronized with seasonal water levels, with flowering and seed production occurring as waters recede. These plants rely solely on sexual reproduction, making pollination a key evolutionary driver for diversification. Different pollination strategies, melittophily, anemophily, and self-pollination have been reported within the family. However, integration of floral morphology and pollination biology remains limited. Thus, an overview of reproductive characters in Podostemaceae is presented, focussing on characters that are useful in understanding the pollination strategies and functional floral morphology in the family. This review synthesizes current knowledge to explore how pollination systems and floral traits have shaped the evolutionary trajectory of Podostemaceae.